Inability to switch from ARID1A-BAF to ARID1B-BAF impairs exit from pluripotency and commitment towards neural crest formation in ARID1B-related neurodevelopmental disorders - Luca Pagliaroli; Patrizia Porazzi; Alyxandra T. Curtis; Chiara Scopa; Harald M. M. Mikkers; Christian Freund; Lucia Daxinger; Sandra Deliard; Sarah A. Welsh; Sarah Offley; Connor A. Ott; Bruno Calabretta; et al. (Nature Communications, 2021)
Mutations in the ARID1B subunit of the BAF chromatin remodeling complex are associated with the neurodevelopmental Coffin-Siris syndrome. Here the authors reveal that there is a transition from ARID1A-containing complexes to ARID1B during cranial neural crest cell differentiation that is impaired in Coffin-Siris patient-derived cells, which is important for exit from pluripotency.